Spatial and profile distribution of mercury in soils of natural landscapes - Beznosikov, Vasiliy; Lodygin, Evgeniy; Nizovtcev, Andrey (Biological Communications, 2013)
The article analyses the content of bulk forms of mercury in soils of natural landscapes. The character of distribution of mass fraction of mercury for soils of taiga zone is characterized by regressive-accumulative type. The soils of accumulative landscapes are rich in mercury in contrast to that of eluvial ones. It was shown that migratory ability of mercury is mainly determined by quantity of organic matter and grain texture. A database on mass fraction of mercury in the soils was composed using the GIS-technologies and the corresponding mercury distribution map was produced.